Cultural System of Religious Beliefs. State of the Art (2019)
In this review, a documentary research of a qualitative nature is carried out, whose main objective is to establish a state of the art on the subject of cultural systems of religious beliefs. For this, a methodological route was drawn up that took into account fourmoments: documentary review; classification of studies in academic research, research books and scientific articles; categorization; and subsequent analysis, interpretation and evaluation of the theoretical and methodological approaches. As results, it can be seen that there is a virtually unexplored field of research that must be valued through new research